Modulation of STAT-3 in rheumatoid synovial T cells suppresses Th17 differentiation and increases the proportion of Treg cells - Ju, Ji Hyeon; Heo, Yu-Jung; Cho, Mi-La; Jhun, Joo-Yeon; Park, Jin-Sil; Lee, Seon-Yeong; Oh, Hye-Jwa; Moon, Su-Jin; Kwok, Seung-Ki; Park, Kyung-Su; Park, Sung-Hwan; Kim, Ho-Youn (Arthritis & rheumatology (Hoboken, N.J.), 2012)
Objective To investigate the impact of STAT‐3–mediated regulation on Th17 differentiation in patients with rheumatoid arthritis (RA). Methods CD4+ T cells isolated from peripheral blood (PB) and synovial fluid (SF) were stimulated to differentiate into Th17 cells or Treg cells. The activity of STAT‐3 was knocked down by transfecting CD4+ T cells with small interfering RNA (siRNA). After 3 days in culture, the proportions of Th17 cells and Treg cells were measured by flow cytometry, and the production of interleukin‐17 (IL‐17) was measured by reverse transcriptase–polymerase chain reaction and enzyme‐linked immunosorbent assay. Results The levels of IL‐17, IL‐6, IL‐23, IL‐1, and tumor necrosis factor α were significantly higher in RA SF and synovial tissue than in SF and synovial tissue from osteoarthritis patients. In RA synovial tissue, the expression of STAT‐3 increased in proportion to the severity of synovitis, as shown by stromal cellularity, intimal hyperplasia, and inflammatory infiltration. The degree of Th17 differentiation was highest in RA SF, followed by RA PB, and lowest in normal subjects. In CD4+ T cells, transfection with STAT‐3 siRNA prevented Th17 differentiation of mononuclear cells from RA PB and SF but increased the proportion of Treg cells. In contrast, inhibition of STAT‐5, the transcription factor for Treg cells, increased the proportion of Th17 cells and reduced that of Treg cells. Conclusion Our findings indicate that modulation of STAT‐3 in CD4+ T cells affects the differentiation of Th17 cells and Treg cells in patients with RA. This role of STAT‐3 in RA synovial T cells may provide a new therapeutic target for the management of RA.